2004
DOI: 10.1016/j.biolcel.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Fertilization: From Sperm Factor to Phospholipase Cζ

Abstract: In mammalian eggs, the fertilizing sperm evokes intracellular Ca 2+ ([Ca 2+ ] i ) oscillations that are essential for initiation of egg activation and embryonic development. Although the exact mechanism leading to initiation of [Ca 2+ ] i oscillations still remains unclear, accumulating studies suggest that a presently unknown substance, termed sperm factor (SF), is delivered from the fertilizing sperm into the ooplasm and triggers [Ca 2+ ] i oscillations. Based on findings showing that production of inosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 122 publications
1
48
0
Order By: Relevance
“…This difference was not significant as determined by Mann-Whitney rank sum test (PZ0.561). These results are consistent with the recently published experiments testing these fusion proteins in eggs activated by normal fertilization (Kurokawa et al 2004a, Mehlmann & Jaffe 2005 (Sakakibara et al 2005), the sperm-induced calcium transient (Abassi et al 2000), pronuclear migration and fusion (Moore & Kinsey 1995, Wright & Schatten 1995, as well as developmental competence (Livingston et al 1998, Sharma et al 2005. The extent to which these pathways are active in mammalian fertilization is now the subject of much investigation.…”
Section: Role Of Fyn In Mouse Egg Activationsupporting
confidence: 90%
See 1 more Smart Citation
“…This difference was not significant as determined by Mann-Whitney rank sum test (PZ0.561). These results are consistent with the recently published experiments testing these fusion proteins in eggs activated by normal fertilization (Kurokawa et al 2004a, Mehlmann & Jaffe 2005 (Sakakibara et al 2005), the sperm-induced calcium transient (Abassi et al 2000), pronuclear migration and fusion (Moore & Kinsey 1995, Wright & Schatten 1995, as well as developmental competence (Livingston et al 1998, Sharma et al 2005. The extent to which these pathways are active in mammalian fertilization is now the subject of much investigation.…”
Section: Role Of Fyn In Mouse Egg Activationsupporting
confidence: 90%
“…For example, while mammalian eggs express Fyn, Yes, and in some cases, Src (Talmor et al 1998, Talmor-Cohen et al 2004a), the results of two different studies indicate that these kinases are not required for the unique sperm-induced calcium oscillations (Kurokawa et al 2004a, Mehlmann & Jaffe 2005, which trigger egg activation in mammals (Carroll 2001). Instead, these calcium oscillations are triggered directly by a sperm-borne phospholipase that does not require PTK regulation (Cox et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently shown that expression of cRNAs encoding for PLCZ1 in eggs initiated oscillations reminiscent of those induced by normal fertilization [7,8]. Additional studies demonstrated expression of PLCZ1 in the testes of other mammals and PLCZ1 cRNAs were able to induce oscillations in eggs of homologous and heterologous species including human PLCZ1 into human eggs [7,9,10]. Further, injection of sperm extracts depleted of PLCZ1 failed to initiate oscillations [7,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of development is triggered by a series of long-lasting oscillations of intracellular free calcium ([Ca 2C ] i ). Several pieces of evidence support the hypothesis that the sperm, upon fusion with the oocyte, delivers a sperm-specific isoform of phospholipase C (PLCZ; Saunders et al 2002, Kurokawa et al 2004, 2006, Malcuit et al 2006a. PLCZ has the ability to function at basal Ca 2C concentrations (Kouchi et al 2004) and thus, upon entering the oocyte's cytoplasm, induces hydrolysis of phosphatidylinositol-4, 5-bisphosphate (PIP 2 ), generating 1, 2-diacylglycerol (DAG), and IP 3 .…”
Section: Introductionmentioning
confidence: 99%